2002
DOI: 10.1159/000066758
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Panniculitis in an 88-Year-Old Man with Neuroendocrine Carcinoma

Abstract: Pancreatic panniculitis is a rare complication that occurs in 0.3–3% of patients with pancreatic diseases. Most of the cases reported to date were associated with adenocarcinoma and acute or chronic pancreatitis. We here present an 88-year-old man who was admitted to our institution with a nonfunctional neuroendocrine carcinoma of the pancreas. He subsequently developed pancreatic panniculitis and arthritis. Treatment with octreotide did not have an effect neither on progression of the carcinoma nor on develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 9 publications
2
51
0
1
Order By: Relevance
“…Two cases were insulinoma [7,8] and the other two were identified as nonfunctional NET [9,10]. Like in our patient, cases from previous reports visited the hospital presenting panniculitis with constitutional symptom such as weight loss, anorexia or fatigue.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Two cases were insulinoma [7,8] and the other two were identified as nonfunctional NET [9,10]. Like in our patient, cases from previous reports visited the hospital presenting panniculitis with constitutional symptom such as weight loss, anorexia or fatigue.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, it is suggested that there are mechanisms other than pancreatic carcinoma that cause pancreatic panniculitis. In previous reports, Schwartz and Fleishman [8], Preiss et al [9], and Berkovic and Hallermann [10] described a relatively large mass; 12 cm, 11×13-cm and 5-cm sized NET, respectively. One possible mechanism of pancreatic panniculitis associated with pancreatic NET is that the large mass may cause obstruction of the pancreatic ducts and thus temporarily increase the exocrine enzyme levels, resulting in pancreatic panniculitis.…”
Section: Discussionmentioning
confidence: 91%
“…The delay of 9 months for the diagnosis and treatment worsened the prognosis of this condition. Rarely, other types of pancreatic carcinoma are associated with panniculitis, including islet cell carcinoma 17 , neuroendocrine carcinoma 4,18 and acinar cell cystadenocarcinoma 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The somatostatin analogue octreotide, which inhibits secretion of pancreatic enzymes, can be useful to resolve the skin lesions and arthropathy 19 . However, Preiss and his collegues 18 demonstrated it was ineffective in an 88-year-old man with neuroendocrine carcinoma and whose somatostatin receptor scintigraphy was negative. It has also been demonstrated that corticosteroid, non-steroid anti-inflammatory drugs, and immunosuppressants could effectively not control the symptoms 5,11 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Histologically, the lesions are characterized by lobular panniculitis without evidence of vasculitis. 2,6,7 Adipocytes that have undergone coagulative necrosis are termed ghost adipocytes because they have lost their nuclei. 2 Treatment of pancreatic panniculitis is supportive and directed at the underlying pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%